Transdifferentiation of Integrin Beta 1 High+ Skin Progenitor Cells Into Functional Hepatocytes - Jung Hwa Lim; Dae Hun Kim; Junhee Lee; Cho-Rok Jung; Hyun Mi Kang (Stem Cells International)
A highly reproducible and functional liver model that closely resembles the human liver plays a crucial role in drug development, disease research, personalized medicine, and regenerative medicine. This study aimed to establish an in vitro liver model using skin epidermal progenitor cells (EPCs), which are easily accessible and exhibit a high proliferative capacity. Skin EPCs with high integrin beta 1 expression demonstrated multipotent differentiation potential, capable of differentiating into adipocyte- and neuron-like cells in vitro. Furthermore, when exposed to high concentrations of activin A, along with Wnt3a and BMP4, these cells efficiently differentiated into definitive endoderm, exhibiting high FOXA2 expression. Under our culture conditions, they further differentiated into functional hepatocytes. These differentiated cells exhibited high albumin secretion, CYP activity, and drug metabolism capabilities similar to those observed in vivo. In conclusion, this study highlights the potential of EPCs to differentiate into functional hepatocytes, providing a feasible and scalable source of hepatocytes for drug screening, liver disease modeling, and potential cell-based therapies.